Does U.S. Immigration Policy Facilitate Financial Misconduct? - Dai, Ruiting; Dong, Xuanjun; Shroff, Nemit; Tan, Qin (Journal of Accounting Research, 2025)
ABSTRACT We examine whether U.S. immigration policy, specifically the H‐1B visa program, affects the likelihood of financial misconduct. We argue that employers have leverage over employees on H‐1B visas because such employees must maintain H‐1B–eligible employment to legally reside in the United States. We posit that companies relying on H‐1B visas to hire workers in accounting roles have an increased ability to misreport their financial statements due to the greater costs H‐1B employees face if they are unexpectedly fired for not following the demands of their bosses or for blowing the whistle on misconduct. Using the sharp reduction in the H‐1B visa cap in 2004 as a shock to such employment, we find that companies that relied on this visa program for accounting roles pre‐shock experience a 2.3 percentage point decline in accounting irregularities post‐shock. Cross‐sectional tests show that the reduction in irregularities is greater in companies where H‐1B employees have (1) a greater influence on financial reporting or (2) fewer job opportunities. In addition, the relation between H‐1B visa use and irregularities is stronger in companies whose investors are more focused on near‐term earnings targets. We corroborate our findings using the outcome of H‐1B visa lotteries as shocks to such employment.